Ecological mapping of the impacts derived from the construction and operation of Egnatia highway at Xanthi prefecture after the analysis and processing of vector and raster data of the area through Geographic Information Systems, as well as with the preparation of the environmental impact study of the project. - Koumoulidis, Dimitrios; Efthimiadou, Aspasia (My University, 2020)
Road infrastructure plays a significant key role of development policies that are directly related to social, economic and territorial cohesion of states, but also the European Union as a whole. Given the need for road infrastructure, as is noted also at the White Paper of the European Community (Commission of the European Communities, 2001), a parallel ecological vision of road projects, can seriously raise issues of changes and alterations these projects may bring to the natural environment. Besides the loss of habitat, those projects can cause disturbance and changes in the amount and the balanced physical connectivity. It is important to note the alteration of hydrological processes of areas susceptible to these projects. These infrastructures impact in a negative way on ecological processes, creating species extinction conditions, migration and a total modification of genetic material, with a significant impact on food chains and the overall biodiversity of areas which hold those projects. In Greece, one of the largest road construction projects is that of the Highway Egnatia, which has even been included in the Trans-European Road Transport Networks priority. The highway of 670 km crosses the entirety of Northern Greece by connecting urban centres, ports and airports succeeding in reducing time travel and so providing better access to remote areas and populations closer to large urban centres. In this study, with the help of geographic information systems, an analysis of spatial data of the study area is carried out, as an effort to record and assess the ecological footprint of the construction and the operation of the Egnatia highway, the changes, the rearrangements and the risks that may cause in both the human environment and the wider natural environment of such a rich ecological area. Supplementary tool for final conclusions and decisions in the current study, is the preparation of the Environmental Impact Study (EIS) of the project, identifying the different types of ecosystems in the region affected by the Egnatia highway. Then follows an assessment of the expected losses and pressures on the ecology of the area, using the technique of descriptive lists. Part of the results in this present study, document the low level of burden and deterioration of environmental and anthropogenic variables, which are in connection with the construction and operation of the Egnatia highway in the study area county. It appears that the most likely negative effects of the project, concern the area of Nestos River, with habitats cut-off phenomena, transforming landscape and the disturbance of wildlife.
Keywords: Road infrastructure; Geographic information systems; Environmental impact assessment; Descriptive checklists